Manajemen Kepemimpinan Inovatif Pada Pendidikan Dalam Perspektif Merdeka Belajar Era New Normal - Putu Ida Arsani Dewi (Edukasi: Jurnal Pendidikan Dasar, 2022)
This research is motivated by the findings of a lack of innovative leadership management in school principals at the early childhood education level. The purpose of this study is to describe innovative leadership management in primary school education in the perspective of independent learning in the new normal era in Singaraja City. Using quantitative descriptive research methods. The data sources consist of 38 school principals. The results showed that the innovative leadership of school principals in Singaraja City was in the good category. The novelty found in this research is that future school principals must have a more revolutionary spirit able to accept and implement changes through the vision, mission, and goals to develop the school. The impact of the results of this study is that school principals need to work together with teams through team creativity and organizational innovation as well as a systematic way of working in organizational innovation through individual creativity, visually understanding actual information digitally to realize independent learning for now and the future.front.